Development of an air bearing test rig - Yang, Rui Fang (2009)
Air bearings play an increasingly important role in the future development of hard disk dependent devices. A comprehensive review on the working principle of the air bearing will be presented in this report. With the increasing need for faster and more mobile disk storage devices, air bearing offers significant advantages over oil lubricated bearings. It uses air as its lubricant, making it cleaner. Air, with a lower viscosity, produces less frictional resistance as compared to oil lubricant. Hence, the performance and characteristics of the air bearing are earnestly examined. However, the miniature size of the air bearings poses a major challenge for the examinations of the air bearing’s operating characteristics, for instance load carrying capacity and gas film thickness. Therefore, there is a need to develop an air bearing of a larger scale, for experimentation on the operating characteristics of air bearing. A test rig is designed and developed with a scaled up air bearing. The optimum parameters used in a normal air bearing are used to obtain the bearing number, which is held constant during the design of the scaled up model. The details of the designs are presented and the dimensions for the components are documented. The test rig is then fabricated and the process is documented. The completed prototype is then shown and further possible improvements that can be made to the design are being discussed at the last part of the report.